Perancangan Sistem Informasi Barang Bukti Dan Barang Temuan Tindak Pidana Pada Cabang Kejaksaan Negeri Deli Serdang - Atika Sari br pa; Muhammad Dedi Irawan (Journal Of Informatics And Busisnes, 2024)
As a part of a government agency, the use of information systems is very important in assisting the performance of the Deli Serdang District Prosecutor's Office Branch in Pancur Batu. At the Deli Serdang District Prosecutor's Branch in Pancur Batu, inputting evidence and found items is still done manually, that is, just by taking notes, so there are difficulties and it is also very time consuming when you want to see or look for information regarding the evidence or found items. For this reason, the Deli Serdang District Prosecutor's Office Branch in Pancur Batu needs an effective and efficient system for managing information regarding evidence and found items. The aim of this research is to make it easier to input data and find information about the evidence and findings that we want. In this research I used the waterfall method, this method is one of the most experienced and easiest programming improvement models, this method includes the stages of system requirements analysis, system design, implementation, testing and maintenance. The results of this research, namely the output on the report page, prove that the system is running well and at the testing stage the Information System Application for Evidence and Found Items can work as desired. And at the testing stage it is carried out using the Black Box testing method. From the test results, the system runs well so that the Evidence and Found Items Information System application can be used.